Perancangan Enterprise Architecture Berbasis Togaf ADM Untuk Integrasi Sistem Menggunakan ODOO ERP pada PT Bromindo Mekar Mitra - Suluh Hidayat; Heni Candra Kirana; Himawan Wicaksono; Kristiawan Nugroho (SENTRI: Jurnal Riset Ilmiah, 2026)
Digital transformation requires organizations to implement integrated and adaptive information systems capable of supporting end-to-end business processes. PT Bromindo Mekar Mitra currently utilizes several applications, such as Firecek Backoffice, Bisma, Pembukuan, Trello, and Oteem to support its operations. However, these systems operate independently (stand-alone), resulting in data duplication, reporting delays, and information inconsistencies across divisions. This condition indicates an urgent need for a strategic and structured architectural approach to achieve system integration aligned with the company’s business requirements. This study aims to design an Enterprise Architecture (EA) as a foundation for system modernization and integration using the Odoo ERP platform. The TOGAF Architecture Development Method (ADM) framework is employed to analyze the As-Is architecture, develop the To-Be architecture, and formulate a comprehensive implementation roadmap. Data collection was conducted through interviews, business process observations, and analysis of internal documentation. The research results include integrated business, data, application, and technology architecture designs, as well as recommendations for Odoo ERP modules that align with PT Bromindo Mekar Mitra’s operational needs. The resulting EA blueprint and migration roadmap are expected to serve as strategic guidance for the company in implementing system integration in a gradual, measurable, and sustainable manner while minimizing the risks associated with ERP adoption.